Design of DDS based on Hybird-CORDIC Architecture - Yubin Zhang; He Chen; Yingtao Ding; Xiujie Qu (International Journal of Computational Intelligence Systems, 2011)
Communication technology and its signal processing are basic supportive factors of intelligent transportation system. Because of rapid progress in modern communication engineering, direct digital synthesizer (DDS) is widely used in communications system. However, traditional DDS technology is encountering challenges due to its ROM's capacity limit. The paper presents a new direct digital frequency synthesizing method based on Hybird-CORDIC (coordinated rotation digital computing) algorithm, which can calculate sin/cos value directly, improve performance, reduce size, and reduce design complexity. Accordingly, the result of field-programmable gate array (FPGA) realized with Verilog HDL language is in accord with expected requirement approvingly.